SOME DETERMINATION RIS KS APPROACH OF MEDICAL INSURANCE ACTIVITY (FIRST REPORT) - S. O. Dzhundubayeva; L. Yu. Babintseva (Medična Informatika ta Inženerìâ, 2013)
The risks of medical insurance activity researches are generalized. The dynamics of statistical indices to purchase medical services for population are analyzed in the first report. The peculiarities of risk estimation in connection with the expressed vagueness of similar tasks are underlined.